The Needs of High Order Thinking Skills-Oriented Student Worksheets on The Human Circulation System Materials For Grade XI Students - Shafira, Fitri; Ristiono, Ristiono; Alberida, Heffi; Yogica, Relsas (Thinking Skills and Creativity Journal, 2022)
The 2013 curriculum is designed to produce a generation that is ready and able to face the challenges of the 21st century. The challenges of the 21st-century demand qualified and competent human resources. The 2013 curriculum requires students to be able to think at a high level (High Order Thinking Skills). Based on the results of observations found the fact that there are no learning media that can improve students' higher-order thinking skills. Therefore, a HOTS-oriented Student Worksheet was developed on the material of the circulation system in the human body. This study aims to analyze the need for High Order Thinking Skills-oriented Student Worksheets about the material for the circulation system in the human body for students of class XI SMA. The study was conducted using a survey method using a questionnaire distributed to students and biology teachers. The study was conducted using a survey method using a questionnaire distributed to students and biology teachers. The questionnaire was filled out by 63 students of class XI MIPA and one biology teacher. The questionnaire results show that students have difficulty studying the material for the circulatory system in the human body because this material contains many confusing terms, and the material is rote. Students agree that the use of student worksheets when learning can help students in learning. The development of HOTS-oriented worksheets can be a solution to the problems faced by students in the material of the circulatory system in the human body.